The antecedents and consequences of autonomous and controlled motivation: Domain specificity and motivational sequence at the situational level - Paumier, Delphine; Chanal, Julien (Frontiers in Psychology, 2022)
The aim of this study was to investigate the level of specificity of the different regulation types described by Self-Determination Theory, and to evaluate its impact on the links with its antecedents and consequences, in an academic context. In line with the school-subject-specificity hypothesis, we postulated that autonomous motivation types (AM types) would be more specific to the situational level than controlled motivation types (CM types). Moreover, we hypothesized that AM types would be, at this level, more strongly associated with its antecedents and consequences than CM types. Three hundred fourteen university students were asked to complete online questionnaires assessing their motivation, motivational antecedents (i.e., autonomy-supportive climate and self-concept) and consequences (i.e., emotions and grades) in various courses. As expected, results from structural equation modeling confirmed that AM types were more specific to the situational level than CM types. Moreover, a higher number of significant correlations were found between motivation and its antecedents and consequences in the corresponding course for AM than for CM types. Educational implications and directions for future research are discussed.